2014
DOI: 10.1002/ece3.1297
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the thermal physiology of adult Yarrow's spiny lizards (Sceloporus jarrovii) in relation to sex and body size

Abstract: Sexual size dimorphism (SSD) is often assumed to reflect the phenotypic consequences of differential selection operating on each sex. Species that exhibit SSD may also show intersexual differences in other traits, including field-active body temperatures, preferred temperatures, and locomotor performance. For these traits, differences may be correlated with differences in body size or reflect sex-specific trait optima. Male and female Yarrow's spiny lizards, Sceloporus jarrovii, in a population in southeastern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 66 publications
2
38
0
Order By: Relevance
“…E. kosciuskoi lizards were significantly faster than P. entrecasteauxii lizards (Figure 1c). This is most likely due to their smaller size (Beal et al 2014). Between the sprint capacities of the male, female and gravid individuals, no significant difference was discerned for either species, which is also consistent with the Beal study (Figures 2a and 2b), though it suggests the higher thermal preference of gravid females (Schwarzkopf and Shine 1991) does not result in a significant increase in speed.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…E. kosciuskoi lizards were significantly faster than P. entrecasteauxii lizards (Figure 1c). This is most likely due to their smaller size (Beal et al 2014). Between the sprint capacities of the male, female and gravid individuals, no significant difference was discerned for either species, which is also consistent with the Beal study (Figures 2a and 2b), though it suggests the higher thermal preference of gravid females (Schwarzkopf and Shine 1991) does not result in a significant increase in speed.…”
Section: Discussionsupporting
confidence: 85%
“…As temperatures increase, the thermal tolerances of the region's biota become increasingly important (Root et al 2003;Pickering et al 2004). The fitness of reptile species is closely correlated with temperature, and sprint speed capacity may be used as an indicator for lizard fitness (Beal et al 2014). For the two lizard species studied fitness as measured through sprint speed was shown to increase at an elevated temperature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beal et al (2014) found that body temperatures of Sceloporous jarrovii varied between sexes: it is possible that the data are only representative of female lizards.…”
Section: Discussionmentioning
confidence: 99%